Perception and use of digital tax services: A case study - Dote-Pardo, Jairo; Marín Chavez, Yenifer; Saavedra-Espinosa, Patricio (RAN - Revista Academia & Negocios, 2025)
Purpose: The purpose of this study is to analyze the factors that influence the adoption and use of the Chilean Internal Revenue Service’s (IRS) online platform, a critical tool to improving accessibility and optimizing tax compliance. Methodology: Data was collected through a questionnaire applied to a sample of 386 IRS users in one of Chile’s administrative regions. Contingency tables were constructed, and chi-square tests were applied to evaluate user perceptions and statistical significance. Results: Significant differences in platform participation are observed. Higher education levels and urban residence are associated with higher participation, while older adults and rural residents face barriers. Key impediments include the complexity of procedures and difficulties in navigation, particularly for lower tax brackets. Implications: Improving the interface, simplifying procedures and expanding training are essential to increasing the adoption and usability of the IRS platform, as they facilitate user interaction and reduce technical barriers. Originality: This study provides empirical evidence on digital adoption in southern Chile, highlighting the barriers of marginalized communities and providing recommendations for digital inclusion in emerging economies.